Technological Options for the Production of Health-Promoting Proteins and Peptides Derived from Milk and Colostrum - Korhonen, H.; Pihlanto, A. (Current Pharmaceutical Design, 2007)
Milk proteins are known to exert a wide range of nutritional, functional and biological activities. Apart from being a balanced source of valuable amino acids, milk proteins contribute to the consistency and sensory properties of various dairy products. Furthermore, many milk proteins possess specific biological properties which make them potential ingredients of health-promoting foods. These properties are attributed to both native protein molecules and to physiologically active peptides encrypted in the protein molecules. Considerable progress has been made over the last twenty years in technologies aimed at separation, fractionation and isolation in a purified form of many interesting proteins occurring in bovine colostrum and milk. Industrial-scale methods have been developed for native whey proteins such as immunoglobulins, lactoferrin, lactoperoxidase, α-lactalbumin and β-lactoglobulin. Their large-scale manufacture and commercial exploitation is still limited although validated research data about their physiological health benefits is rapidly accumulating. Promising product concepts and novel fields of use have emerged recently, and some of these molecules have already found commercial applications. The same applies to bioactive peptides derived from different milk proteins. Active peptides can be liberated during gastrointestinal digestion or milk fermentation with proteolytic enzymes. Such peptides may exert a number of physiological effects in vivo on the gastrointestinal, cardiovascular, endocrine, immune, nervous and other body systems. However, at present the industrial-scale production of such peptides is limited by a lack of suitable technologies. On the other hand, a number of bioactive peptides have been identified in fermented dairy products, and there are already a few commercial dairy products enriched with blood pressure-reducing milk protein peptides. There is a need to develop methods to optimise the activity of bioactive peptides in food systems and to enable their optimum utilisation in the body. This review highlights existing modern technologies applicable for the isolation of bioactive native proteins and peptides derived from bovine colostrum, milk and cheese whey, and discusses aspects of their current and potential applications for human nutrition and promotion of human health.
Keywords: health promotion